2021
DOI: 10.3390/app11093840
|View full text |Cite
|
Sign up to set email alerts
|

Alkali-Activated Binders Using Bottom Ash from Waste-to-Energy Plants and Aluminium Recycling Waste

Abstract: Alkali-activated binders (AABs) stand out as a promising alternative to replace ordinary Portland cement (OPC) due to the possibility of using by-products and wastes in their manufacturing. This paper assessed the potential of weathered bottom ash (WBA) from waste-to-energy plants and PAVAL® (PV), a secondary aluminium recycling process by-product, as precursors of AABs. WBA and PV were mixed at weight ratios of 98/2, 95/5, and 90/10. A mixture of waterglass (WG) and NaOH at different concentrations (4 and 6 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…It is expected than more of 1 Mt per year of this kind of by-product are generated in Europe. It is mainly composed of aluminium-rich oxide and hydroxide phases [46,47].…”
Section: Raw Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is expected than more of 1 Mt per year of this kind of by-product are generated in Europe. It is mainly composed of aluminium-rich oxide and hydroxide phases [46,47].…”
Section: Raw Materialsmentioning
confidence: 99%
“…Recent studies have shown the potential applications of PV in the cement, ceramic, refractory, and building industries [44][45][46]. PV is also used as a precursor source in alkali activation technology because of its high reactive aluminium content [45][46][47]. In this sense, its commercialisation is subject to its chloride content, which cannot be higher than 2%, otherwise, it could only dispose of in a landfill [48].…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that the valorization of steel and aluminum recovered from IBA enables great energy savings in the steel and aluminum industries, which are energy-intensive sectors. Moreover, the utilization of IBA to produce cement reduced the consumption of natural resources [90,119,120]. Silva et al [11] provided a literature review regarding the environmental performance of the utilization of IBA in construction-related products.…”
Section: Potential Drivers Barriers and Prospects For Iba Usementioning
confidence: 99%
“…Therefore, the scientific community continues to study potential applications for the valorization of IBA, to increase its value-added potential. Some of these potential applications focus on the use of IBA as a precursor in alkali-activation technology [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%